PENTINGNYA VARIASI TATA LETAK DAN GARNISH PADA HIDANGAN TERHADAP TINGKAT KEPUASAN TAMU DI HOTEL HORISON ULTIMA MALANG - antonius bayu kartiko (Jurnal Pariwisata Pesona, 2016)
In food presentation, especialy in a restaurant and a hotel, required human resource who have artistics soul, creativity, and high profesionalism. Thus food layout and garnish variation can increase guests satisfaction. But now food layout and garnish are often forgotten. The writter want to know the importance of food layout and garnish for guest satisfaction and guests response to food that are served. The Writter used primary and secondary data collections method and then analyzed using descriptive-qualitative method. The lack of human resources who understand the art of food production, limit variety of food layout and garnish. And then increase guests surfeit who have become rugular guest. For the guests food layout and garnish are important think and proportional against guests satisfaction.